Estimation of the Surface Net Radiation Under Clear-Sky Conditions in Areas With Complex Terrain: A Case Study in Haihe River Basin - Liu, Xingran; Zhang, Jing; Yan, Haiming; Yang, Huicai (Frontiers in Ecology and Evolution, 2022)
The surface net radiation as an important component of the surface radiation budget has attracted wide attention, however, it is still an enormous challenge to carry out accurate estimation of the surface net radiation in areas with complex terrain due to the scarcity of radiation observation sites and high spatial heterogeneity of influencing factors of the surface net radiation. Taking the Haihe River Basin as the study area, this study estimated the surface net radiation under clear-sky conditions during 2001 2019 based on improved algorithm of the net long-wave radiation, and the solar short-wave radiation in terms of direct radiation, diffuse sky radiation and reflected radiation from the surrounding terrain. In this study, the regional meteorological factors were inverted based on remote sensing data to make up for the deficiency of meteorological factor interpolation. The solar short-wave radiation was corrected by considering the comprehensive influence of atmosphere, underlying surface and terrain, and the net long-wave radiation was optimized by localizing the algorithm coefficients. Results showed the correlation coefficient between the estimated and observed surface net radiation reached approximately 0.9, indicating the accuracy of this improved method is acceptable. Besides, the results suggested the surface net radiation was significantly influenced by the terrain, the highest value of which occurred on the south slope, followed by that on the southwest slope, west or southeast slopes, and the lowest value occurred on the north slope. In addition, there was the highest surface net radiation in summer, and there was the lowest and frequently negative surface net radiation in winter. This study makes up for the shortcomings of traditional spatial interpolation of meteorological factors and previous empirical formulas and can therefore provide an important methodological foundation for the research on the surface radiation, climate and hydrology in areas with complex terrain.